Colour pattern predicts outcome of female contest competition in a sexually monomorphic fish. (30th November 2018) - Ziegelbecker, Angelika; Richter, Florian; Sefc, Kristina M.
Abstract : Selection arising from social competition over non-mating resources, i.e. resources that do not directly and immediately affect mating success, offers a powerful alternative to sexual selection to explain the evolution of conspicuous ornaments, particularly in females. Here, we address the hypothesis that competition associated with the territoriality exhibited by both males and females in the cichlid fish Tropheus selects for the display of a conspicuous colour pattern in both sexes. The investigated pattern consists of a vertical carotenoid-coloured bar on a black body. Bar width affected the probability of winning in size-matched female–female, but not male–male, contests for territory possession. Our results support the idea that the emergence of female territoriality contributed to the evolution of sexual monomorphism from a dimorphic ancestor, in that females acquired the same conspicuous coloration as males to communicate in contest competition.